Smoking Cessation Counseling: Practices, Determinants, and Barriers in a Sample of Iranian Primary Care Dentists - Mohammad Reza Khami; Parvin Bastani; Shabnam Varmazyari (Tehran University of Medical Sciences, 2024)
Objectives: Despite the successful tobacco smoking cessation counseling (TSCC) efforts of dental professionals, Iranian primary care dentists have not fully utilized their potential for TSCC provision. Thus, this study assessed the TSCC practices and their associations with socio-professional attributes, knowledge, and attitude, and explored the TSCC barriers and their socio-professional determinants in a sample of Iranian primary care dentists. Materials and Methods: This cross-sectional study was conducted at Comprehensive Healthcare Centers (CHCs) in Tehran Province, Iran from March to June 2019. All dentists practicing in these centers (n=190) completed self-administered questionnaires regarding TSCC-related knowledge, attitude, practice, and barriers. Simple and multiple linear regression and multiple logistic regression tests were used for statistical analyses. Results: The respondents (n=180, response rate=93%) were predominantly females (81.6%), recent graduates (69.6%), and non-cigarette smokers (90.2%), with a mean age of 34±9.98 years. Most performed 'Ask' (90.6%) and 'Advise' (69.1%), while a few were engaged in 'Assess' (33.7%) and fewer in 'Assist,' with 21.3% making physician referrals and 31.5% making psychologist referrals. Non-smokers (B=0.80, 95% CI: 0.19 to 1.40; P=0.01), and those with a more positive attitude (B=0.06, 95% CI: 0.04 to 0.08; P< 0.001) were more likely to provide TSCC. The main identified barriers included "absence of educational resources for patients", "time constraints", and "lack of patient cooperation. Conclusion: Although the selected sample of Iranian primary care dentists performed "Ask" and "Advise" more frequently than their peers, their TSCC practice required further improvement through simplified guidelines, customized pathways, training, team work, and resource advocacy.